The effect of trimetazidine on left ventricular function and hospitalisation in ischaemic heart failure patients in Hospital Universiti Sains Malaysia - Mojolou, Roberta Angelo (2021)
Background : Trimetazidine is primarily used in persistent angina in ischaemic heart disease patients. A few studies showed the potential benefit of trimetazidine in heart failure patients. They were mainly in patients with IHD, DM, and/or elderly patients. Trimetazidine has shown to improve LVEF and hospitalization in this group of patients. Nevertheless, trimetazidine is yet to be used as a first line therapy for heart failure patients with IHD. Objective of this study was to see the effect of trimetazidine on LVEF in IHD patients with reduced EF and hospitalization as well. Methods : This is a comparative cross-sectional study to assess the effect of trimetazidine if added to conventional treatment in patients with IHD with heart failure. This study was conducted from November 2020 until March 2021. Convenient sampling was used, and samples were divided into trimetazidine group and non-trimetazidine arm (control). Patients were recruited from cardiology clinic in HUSM. Baseline data such as EF, age, gender, comorbidities and medications at baseline were obtain retrospectively from patients’ folder. The baseline echocardiography was taken during diagnosis or within one month after starting medications. Subsequently, a follow up echocardiography was obtained after at least 6 months of therapy. Results of LVEF changes were presented as median + IQR and divided into trimetazidine and control group. Differences in median values between independent groups were assessed using Mann-Whitney Test and categorical variables were compared by chi-square test. For two dependent variables, we applied the Wilcoxon Signed Ranks Test. Meanwhile, the Poisson regression was used to predict numbers of hospitalization within 2 years post trimetazidine treatment. Results : Among 139 patients, 73 patients were on trimetazidine and 66 without. Baseline characteristics such as medications and duration of therapy was not statistically significant. There was a statistically significant median difference of ejection fraction at follow up with or without trimetazidine treatment (36% (IQR 6.5%) vs 33% (IQR 13%) respectively, p < 0.001). There was also statistically significant median difference of ejection fraction percentage at baseline and follow up post trimetazidine treatment (33% (IQR 9%) to 36% (IQR 6.5%), p<0.001). Patient who received trimetazidine has OR of 0.78 (95% CI, 0.41 to 1.45) less risk of hospitalization, however tt was not statistically significant (p = 0.43). Conclusion : This small study suggests that trimetazidine addition to standard therapy had positive effect on LVEF after 6 months. However, there was no difference in risk of hospitalization. Trimetazidine may have some role in treatment of patient with heart failure however, further randomized control trial needs to be done to confirm these findings and evaluate on the risk of hospitalization.